Puppet Animation as a Modification of Anecdotal Text Learning Media for Class X SMA - Nia Hariani; Nur Syamsiyah (2021)
Puppet animation is a modification of the appearance of puppet shows into a learning medium, especially for anecdote text material. This study aims to determine the utilization of puppet animation media for students anecdote writing skills. The method used in this research is descriptive qualitative. The subjects in this study were 36 anecdote texts written by students of Grade X Social Science 3 of the State Senior High School 11 of South Tangerang City, Academic Year 2020/2021. Data collection techniques in this research use four ways, such as observation, tests, interviews, and documentation. The assessment aspects used in this study are content, structure, language, as well as spelling and mechanics.This results indicate that there was a positive influence and anecdote writing skills of students using puppet animation media with an average grade of 83, which is well qualified. This proves that in general, students are capable in writing anecdote text well with puppet animation media .Ã‚Â